PERNIKAHAN DINI DI MADURA DALAM NOVEL TARIAN DI RANJANG KYAI KARYA YAN ZAVIN AUNDJAN - Supratman, Muhammad Tauhed; Riani, RN (BEBASAN Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Novel as one of literary works that offers various problems of life both economically, socially and even tradition. Traditionally speaking, this Tarian novel on the Kyai Bed by Yan Zavin Aundjan also discusses traditions that take place in the community, especially the Madurese. This tradition is a tradition of early marriage. This research is qualitative research, while data and data sources used in this study are dance novels on the Kyai Bed by Yan Zavin Aundjan. The method used in this research is descriptive method. Descriptive method is a method that describes or describes the facts or symptoms systematically about the tradition of early marriage of Madurese people in the dance novel on the Kyai Bed by Yan Zavin Aundjan. Data collection techniques are done by documentation techniques. The data analysis technique was carried out by coding, classification, interpretation and description of the data on the tradition of early marriage of the Madurese community in the Tarian novel on the Kyai Bed by Yan Zavin Aundjan. The results of the analysis show that the early marriage tradition in the Tarian novel on the Bed of the Kyai by Yan Zavin Aundjan was characterized by several factors, namely the compulsion factor of parents, low education level, poverty and economic pressure, and custom that occurred in the characters Misnadi, Nisa, Iqbal, and Suci.